Prospects of the use of pe¬at tab¬lets at growing of planting stock of oak ordinary - Guz , Mykola (Forestry, Forest, Paper and Woodworking Industry, 2007)
It is analysed the results of experimental researches of influence of conditions on growing of planting stock on its forming and development in forest cultures.